Spiritual Capital Innovative Work Behavior and Subjective Well Being of Startup Founders - Agustina, Tri Siwi; GENÇ, Abdullah Talha; Prasetyo, Ari (Aptisi Transactions On Technopreneurship (ATT), 2026)
The rapid growth of the startup ecosystem in Indonesia presents substantial opportunities as well as significant challenges for startup founders, particularly in maintaining their subjective well-being. This study aims to examine the effect of spiritual capital on the subjective well-being of startup founders in Surabaya, Indonesia, with innovative work behavior as a mediating variable. This study adopts a quantitative research design using survey data collected from 107 startup founders through a structured questionnaire. The sampling technique employed was convenience sampling. This study employs a reflective measurement model for all latent constructs within the PLS-SEM framework. The findings reveal that spiritual capital has a positive and significant effect on the subjective well-being of startup founders. Furthermore, innovative work behavior partially mediates the relationship between spiritual capital and subjective well-being. These results indicate that spiritual capital not only directly enhances subjective well-being but also indirectly contributes through the promotion of innovative behaviors among startup founders.